Chelation with a twist: a bifunctional chelator to enable room temperature radiolabeling and targeted PET imaging with scandium-44. Issue 2 (11th December 2019) - Vaughn, Brett A.; Ahn, Shin Hye; Aluicio-Sarduy, Eduardo; Devaraj, Justin; Olson, Aeli P.; Engle, Jonathan; Boros, Eszter
Abstract : The small-cavity, bifunctional chelator picaga coordinates Sc-44 at room temperature and enables PET imaging of an in vivo tumor target. Abstract : Scandium-44 has emerged as an attractive, novel PET radioisotope with ideal emission properties and half-life ( t 1/2 = 3.97 h, E mean β + = 632 keV) well matched to the pharmacokinetics of small molecules, peptides and small biologics. Conjugates of the current gold-standard chelator for 44 Sc, 1, 4, 7, 10-tetraaza-cyclododecane-1, 4, 7, 10-tetraacetic acid (DOTA), require heating to achieve radiochemical complexation, limiting application of this isotope in conjunction with temperature-sensitive biologics. To establish Sc(iii ) isotopes as broadly applicable tools for nuclear medicine, development of alternative bifunctional chelators is required. To address this need, we characterized the Sc(iii )-chelation properties of the small-cavity triaza-macrocycle-based, picolinate-functionalized chelator H3 mpatcn. Spectroscopic and radiochemical studies establish the [Sc(mpatcn)] complex as kinetically inert and appropriate for biological applications. A proof-of-concept bifunctional conjugate targeting the prostate-specific membrane antigen (PSMA), picaga-DUPA, chelates 44 Sc to form 44 Sc(picaga)-DUPA at room temperature with an apparent molar activity of 60 MBq μmol −1 and formation of inert RRR -Λ and SSS -Δ-twist isomers. Sc(picaga)-DUPA exhibits a K i of 1.6 nM for PSMA, comparable to the 18 F-based imaging probe DCFPyL ( K i = 1.1 nM) currently in phase 3 clinical trials for imaging prostate cancer. Finally, we successfully employed 44 Sc(picaga)-DUPA to image PSMA-expressing tumors in a preclinical mouse model, establishing the picaga bifunctional chelator as an optimal choice for the 44 Sc PET nuclide.